Composite proportional-integral sliding mode control with feedforward control for cell puncture mechanism with piezoelectric actuation. (May 2022) - Yu, Shengdong; Xie, Mingyang; Wu, Hongtao; Ma, Jinyu; Li, Yao; Gu, Hanlie
Abstract: This paper presents a novel control strategy to compensate hysteretic nonlinearity and achieve precise positioning control of a cell puncture mechanism driven by a piezoelectric actuator (PEA). A dynamic model of the cell puncture mechanism is developed based on the Bouc–Wen model. Parameters of the nonlinear model are identified by particle swarm optimization. The strategy of feedforward (FF) control and sliding mode feedback (FB) control based on the Bouc–Wen inverse model is further developed to position the cell puncture mechanism. Zebrafish embryo is used as the validation object, wherein a cell micropuncture experiment is successfully performed. Proportional-integral sliding mode FB control plus FF control has a simple structure and exhibits excellent performance. Thus, this method can be easily extended to other micro-or nanopositioning mechanisms based on PEAs and adopted in practical applications.